The Apocrypha (Glasgow, Scotland Thomas Murray)
Contains the text of I and II Esdras, Tobit, Judith, The rest of Esther, Wisdom, Ecclesiasticus, Baruch with the Epistle of Jeremiah, The Song of the Three Holy Children, The History of Susanna, The IdolBel and the Dragon, The prayer of Manasses, I and II Maccabees. Includes illustraltions.
Well annotated.
Keywords: Apocrypha -- English translation